2004
DOI: 10.1073/pnas.0406927102
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin suppresses eIF4E-mediated oncogenic transformation by physical mimicry of the 7-methyl guanosine mRNA cap

Abstract: The eukaryotic translation initiation factor eIF4E is deregulated in many human cancers, and its overexpression in cells leads to malignant transformation. Oncogenic properties of eIF4E are directly linked to its ability to bind 7-methyl guanosine of the 5 mRNA. Here, we observe that the antiviral guanosine analogue ribavirin binds to eIF4E with micromolar affinity at the functional site used by 7-methyl guanosine mRNA cap, competes with eIF4E:mRNA binding, and, at low micromolar concentrations, selectively di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
357
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(380 citation statements)
references
References 49 publications
16
357
2
Order By: Relevance
“…Importantly, studies in primary human leukemia specimens suggest that cancer cells overexpressing eIF4E develop an oncogene dependency on eIF4E, making these cells more sensitive to eIF4E inhibition. 31 This type of oncogene "addiction" is similar to observations with other oncogenes such as Her2 and PI3K. 32,33 We serendipitously discovered that a well known anti-viral drug, ribavirin, acts as a cap analogue.…”
Section: Rna Regulons As Therapeutic Targetsmentioning
confidence: 79%
See 2 more Smart Citations
“…Importantly, studies in primary human leukemia specimens suggest that cancer cells overexpressing eIF4E develop an oncogene dependency on eIF4E, making these cells more sensitive to eIF4E inhibition. 31 This type of oncogene "addiction" is similar to observations with other oncogenes such as Her2 and PI3K. 32,33 We serendipitously discovered that a well known anti-viral drug, ribavirin, acts as a cap analogue.…”
Section: Rna Regulons As Therapeutic Targetsmentioning
confidence: 79%
“…Ribavirin treatment impedes eIF4E mediated oncogenic transformation in NIH3T3 cells. 31 Treatment of xenograft mouse models of eIF4E dependent tumours leads to reduced tumour sizes versus untreated controls in our studies with head and neck squamuous cell carcinomas. 31 In mouse models of metastases by Hairisi and colleagues, ribavirin reduced liver metastatic disease.…”
Section: Rna Regulons As Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…149 The antiviral drug ribavirin can block the binding of eIF4E to mRNA. 150,151 Thus, the effects of this compound were examined in some patients with relapsed M4/M5 AML who were no longer eligible for chemotherapy. Although the number of patients in this preliminary trial were low (n ¼ 11), one complete and two partial responders were observed.…”
Section: Pi3k/pten/akt/mtor Drug Resistance and Leukemia Therapymentioning
confidence: 99%
“…The translation initiation factor eIF4E for example has, in addition to its well-described role in the cytoplasm, a nuclear role in the regulation of export of a subset of mRNAs including cyclin D1 (Culjkovic et al, 2005). This function may be involved in the oncogenic function of eIF4E, and both this (Kentsis et al, 2004), and possibly other (O'Shea et al, 2004), selective mRNA export pathways are potential targets for cancer therapy. The proteins involved in the selective export of hdm2 mRNA remain to be identified, however our finding that hdm2 mRNA export is not only dependent upon MEK kinase activity, but is also sensitive to the anti-tumour antibiotic MA in a MEKindependent manner, not only highlight the importance of regulated mRNA export in controlling Hdm2 synthesis, but should also prove useful in the elucidation of its mechanism.…”
Section: Regulation Of Hdm2 By Mithramycin a A Phillips Et Almentioning
confidence: 99%